Democracy in East Asia a new century - Diamond, Larry Jay (Journal of democracy book., 2013)
Predicts that East Asia, with its remarkable diversity of political regimes, economies, and religions, would likely be the critical arena in the global struggle for democracy, a prediction that has proven prescient. This title offers a treatment of the political landscape in both Northeast and Southeast Asia.